If all you need to do is solve for x and y then this is what I would do:
first solving for y
4x^2+3y=y+(1/3) multiply everything by 3 to get rid of (1/3)
12x^2+9y=3y then isolate y
(12x^2)/(-6)=y
then solving for x
go back a few steps to get 12x^2=-6y (this is just rearranging the y= equation)
solve that for x and you should get x=sqrt(-y/2)
i hope this helps- it seems to simple for college algebra, but there you go.
Solving for a variable
4x^2+3y=y+1/3 I'm stuck thanks
2 answers
the 4th line should have been
12x^2+9y=3y + 1
you probably wanted to solve for y, thus expressing it as a function:
6y = -12x^2 + 1
y = -2x^2 + 1/6
12x^2+9y=3y + 1
you probably wanted to solve for y, thus expressing it as a function:
6y = -12x^2 + 1
y = -2x^2 + 1/6